Characterization of odor components of Pixian Douban (broad bean paste) by aroma extract dilute analysis and odor activity values - Hongbin Lin; Yan Liu; Qiang He; Ping Liu; Zhengming Che; Xuemei Wang; Jiaquan Huang (International Journal of Food Properties, 2019)
The odor-active compounds of Pixian Douban (PXDB) were identified by means of gas chromatography-olfactometry (GC-O) coupled with mass spectrometry (MS), and then the key odor components were figured out by odor activity values (OAVs) and aroma extract dilution analysis (AEDA) using three different methods. The 21 odor active areas were detected with flavor dilution (FD) factor ranging from 2 to 16, with 3-(methylthio) propionaldehyde, 2, 5-dimethyl pyrazine, 4-ethyl-2-methoxyphenol, and 2-ethylphenol yielding the highest FD factors. These odorants were then quantitated by application of external standard under selected ion monitoring (SIM) mode of MS, and their OAVs were calculated based on the odor thresholds. The highest OAV was obtained for 3-methylbutanal (malty, 614.89), followed by phenylacetaldehyde (honey-like, sweet, 94.34), four compounds obtained OAVs ≥10, and other eight compounds obtained OAVs between 1 and 10. All of them likely contributed to the aroma of PXDB. A reconstitution model containing 14 odorants (OAVs ≥1& FD>5) was able to mimic the aroma style of the original PXDB. In addition, the application of omission test was used to investigate the effects of the key odor compounds on the whole odor profile of PXDB, and 11 odorants detected were significantly different among the samples.